Strategi Penerapan Pemasaran Digital Marketing Untuk Meningkatkan Laba (Studi Kasus Pada UMKM Warung Tante Syera) - Fittri, Marselly Juanti; Apriadi, Deri (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
. In the face of shifting market dynamics and digital inclined consumer behavior, digital transformation has become a vital necessity for MSMEs. Warung Tante Syera, a small scale grocery business, encounters challenges in leveraging digital platforms for marketing activities. This study aims to develop a tailored digital marketing strategy that encances business profitability. Utilizing a qualitative reserch approach via WhatsApp Business and Shopee along with the marketing mix ($p) and SWOT analysis, led to broadr market reach and more effective customer engagement. Technical assistance and digital training further acclereted technology adoption. The research condludes that context-based digital strategis are key to improving MSME competitiveness anda sustainability. It offers valuable theoretical insights and pratical guidelines for applying costeffectivr, scalable digital marketing strategies in microbusiness contexts. Future research should explore broader MSME samples and incorporate quantitative analysis for greater generalization.